Investigation of the Influence of Matrix Components of Gold Mineral Resources on the Electrochemical Determination of Pt and Re; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Ustinova E. M. Elvira Maratovna (Chemical Engineering and Technology, 2016)
Title screen